Evaluation of moving yellow sticky traps for monitoring and management of whitefly, Bemisia tabaci infesting cotton - KUMAR, RISHI; KRANTHI, SANDHYA; MONGA, D; KUMAR, SANDEEP; SAIN, S K; CHAUDHARY, ALKA (The Indian Journal of Agricultural Sciences, 2019)
Yellow sticky traps (YSTs) are commonly used for monitoring whitefly, Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae), and are usually installed in the crop fields as a stationary unit. In the present investigation YSTs were evaluated as moving unit in association with intercultural operations for their efficacy in monitoring as well as management of whitefly under field conditions. YSTs were moved by different methods in the field along with various intercultural operations such as movement of YSTs attached by rod on either side of the power weeder so as to move just above the crop canopy, movement of YSTs behind two people who would move a rope through the plant rows so as to dislodge sucking pests making the adults stick to the YSTs, YSTs stuck on the pants of the plough operator in the portion just outer to the thigh, and movement of badminton racket covered with YST on both sides between two rows. These methods were compared with YSTs installed as stationary unit, chemical control as well as untreated control. Results of this study suggested that, among all the methods, YSTs installed as stationary unit trapped maximum number of adult whitefly (342±209/trap 24 h after installation) followed by YSTs attached by a rod on either side of the wheels of a plough so as to move just above the crop canopy (236. 95 ±111whitefly adults/trap). No significant correlation between whitefly populations observed on the plants and trapped on the YSTs. Minimal impact on the population dynamics of adult whiteflies was recorded, as YSTs were not able to significantly suppress the population of adult whiteflies when compared with the chemical control. However, YSTs were helpful in early detection of the infestation and minimizing population numerically in comparison to the control plot. Moving YSTs only gave additional advantage of being synchronized with the intercultural operations in cotton.